Substitution of calcium with neodymium and dysprosium in hydroxyapatite structure - Get‘man, E.I.; Loboda, S.N.; Tkachenko, T.V.; Ignatov, A.V.; Zabirko, T.F. (Functional Materials, 2005)
Using X-ray phase analysis, the calcium substitution with Nd and Dy in hydroxyapatite Са₁₀₋xLnx(РО₄)₆(ОН)₂-хОх at 1100°C has been established to take place up to x = 2.0 and 1.4, respectively. The IR spectroscopy has shown that along with the Ca²⁺ +ОH⁻ →
Ln⁺³ + O²⁻ substitution, the 2ОH⁻ O²⁻ + □ one occurs. The structure refinement using Rietveld method has shown that Nd and Dy ions occupy mainly the Ca(2) positions. The Ca²⁺ + ОH⁻ → Ln3⁺ + O²⁻ substitution has been established to strengthening of the Ca(2)-O(4) bond but weakens somewhat the Ca(2)-O(1,2,3) ones. Методом рентгенофазового анализа установлено, что замещение кальция на Nd и Dy в гидроксиапатите Са₁₀₋xLnx(РО₄)₆(ОН)₂-хОх при температуре 1100°С происходит в области до х = 2.0 и 1.4 соответственно. Методом ИК спектроскопии показано, что наряду с замещением Ca²⁺ +ОH⁻ → Ln⁺³ + O²⁻ имеет место и замещение 2ОH⁻ O²⁻ + □. Уточнением структуры методом Ритвельда показано, что ионы неодима и диспрозия занимают преимущественно позиции Са(2). Установлено, что замещение Ca²⁺ + ОH⁻ → Ln3⁺ + O²⁻ приводит к упрочнению связи Са(2)-О(4) и некоторому ослаблению связей Са(2)-0(1,2,3). Методом рентгенофазового аналізу встановлено, що заміщення кальцію на Nd і Dy у гідроксиапатиті Са₁₀₋xLnx(РО₄)₆(ОН)₂-хОх при температурі 1100°С відбувається в області до х = 2,0 і 1,4 відповідно. Методом ІЧ спектроскопії показано, що поряд із заміщенням Ca²⁺ +ОH⁻ → Ln⁺³ + O²⁻ має місце і заміщення 2ОH⁻ O²⁻ + □. Уточненням структури методом Рітвельда показано, що іони неодиму і диспрозію займають переважно позиції Са(2). Встановлено, що заміщення Ca²⁺ + ОH⁻ → Ln3⁺ + O²⁻ приводить до зміцнення зв’язку Са(2)-О(4) і деякому ослабленню зв’язків Са(1)-О(1,2,3).